2020
DOI: 10.1590/1980-5373-mr-2019-0521
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Aurivillius Phase CaBi4Ti4O15 Doped with both La3+ and Mn3+ Cations: Crystal Structure and Dielectric Properties

Abstract: The four-layer Aurivillius CaBi 4 Ti 4 O 15 with introducing of La 3+ on the A-site and Mn 3+ on the B-site with the formula Ca 1-x Bi 3+x LaTi 4-x Mn x O 15 (x = 0, 0.2, 0.4, 0.6, 0.8, and 1) were synthesized by molten salt method using the mixture of sulfate salts K 2 SO 4 /Na 2 SO 4 as the flux. XRD data confirmed the formation of single-phase Aurivillius with A2 1 am orthorhombic structure for x = 0, 0.2, 0.4, and 0.6, whereas for x = 0.8 and 1, the impurity phases were observed. SEM analysis shows the ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
1
6
0
3
Order By: Relevance
“…The significant decrease of c parameter in x ¼ 0.5 might be further raised by the formation of smaller Mn 4þ ions (0.54 Å) compared to Mn 3þ (0.645 Å). A similar trend was also observed in Ca 1-x Bi 3þx LaTi 4-x Mn x O 15 , whereas the formation of Mn 4þ caused a decrease in c lattice parameters and volume cell [14]. The existence of Mn 4þ ions could also be expected to give rise to the magnetic ordering, as discussed further below.…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…The significant decrease of c parameter in x ¼ 0.5 might be further raised by the formation of smaller Mn 4þ ions (0.54 Å) compared to Mn 3þ (0.645 Å). A similar trend was also observed in Ca 1-x Bi 3þx LaTi 4-x Mn x O 15 , whereas the formation of Mn 4þ caused a decrease in c lattice parameters and volume cell [14]. The existence of Mn 4þ ions could also be expected to give rise to the magnetic ordering, as discussed further below.…”
Section: Resultssupporting
confidence: 69%
“…This result shows that the substitution of 12.5% molar ratio La 3þ for Bi 3þ and 12.5% molar ratio Mn 3þ for Ti 4þ can be simultaneously substituted in PbBi 4 Ti 4 O 15 structure when the Pb:Bi ratio is adjusted accordingly. It was previously reported that the single-phase products of the four-layer Aurivillius compounds were obtained for the Mn substitution up to 15% using the molten salt method [9,13,14]. It was inferred that the substitution of Mn 3þ for 15% could be possible.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Fig. 7 shows the temperature dependence of the dielectric constant and dielectric loss of pelletized samples measured in the range 50 kHz to 1 MHz, which best reflects the intrinsic polarizability [35]. The density of the pellets was determined as 7.73 g/cm 3 , 7.57 g/cm 3 , and 7.64 g/cm 3 for PBNO, PBNO-La, and PBNO-Nd respectively, which in each case is greater than 93% of the theoretical density and indicates that the molten salt method produces dense grains [21].…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of the multiferroic Aurivillius phase is challenging since the different characters of d 0 and d n ions with the various ionic radii possibly destroy the structure when partial substitutions are performed [18]. A conventional solid-state method is the most popular method applied in the preparation of the Aurivillius phase.…”
Section: Introductionsmentioning
confidence: 99%